2003
DOI: 10.1080/10810730305682
|View full text |Cite
|
Sign up to set email alerts
|

When a Celebrity Contracts a Disease: The Example of Earvin "Magic" Johnson's Announcement That He Was HIV Positive

Abstract: This meta-analysis summarizes the available data concerning the impact that the public announcement that Earvin "Magic" Johnson, a National Basketball Association All-Star, had tested positive for HIV. The results demonstrate that the announcement increased the level of accurate knowledge in persons, the number of persons getting tested for HIV, and the desire to obtain more information about HIV and AIDS. For adults the impact of the announcement was to increase the perception of vulnerability while for child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 29 publications
2
45
1
Order By: Relevance
“…We found a sharp increase in HIV cure-related public Twitter messages immediately following the announcement. This is consistent with other research on public announcements related to HIV [15,16], and announcements of scientific findings more generally [17][18][19]. However, further research is needed to understand the social psychology of this large social media response (2,786% increase).…”
Section: Hiv Cure Message Sentimentsupporting
confidence: 89%
“…We found a sharp increase in HIV cure-related public Twitter messages immediately following the announcement. This is consistent with other research on public announcements related to HIV [15,16], and announcements of scientific findings more generally [17][18][19]. However, further research is needed to understand the social psychology of this large social media response (2,786% increase).…”
Section: Hiv Cure Message Sentimentsupporting
confidence: 89%
“…Moreover, celebrity announcements can sometimes have paradoxical results. A recent meta-analysis suggested that although Earvin "Magic" Johnson's disclosure of his HIV status increased perceptions of vulnerability among adults it actually was associated with a reduction in perceived HIV risk among children and adolescents (Casey et al, 2003). Goldenring and Purtell (1984) 147 13 Thornhill et al (1986) 365 13 Dachs et al (1989) 633 57 Klein, Berry, and Felice (1990) 66 15 Raghavan (1990) The important finding of association between reports of never having heard of TSE and the intention for delayed health seeking (p = .007) is consistent with data describing the relationship between health knowledge and attitudes and health seeking behaviors among adolescent males.…”
Section: Discussionmentioning
confidence: 99%
“…Fox became a wellknown advocate for Parkinson's disease research after his personal diagnosis. A handful of studies demonstrate that health events and announcements that are associated with a public figure can motivate health information seeking (e.g., Boudioni, Mossman, Jones, Leydon, & McPherson, 1998;Brown & Basil, 1995;Casey et al, 2003;Dean, 2016;Metcalfe, Price, & Powell, 2011). And perhaps not surprisingly given public interest in celebrity gossip, research indicates that celebrity health events also stimulate interpersonal communication about relevant health topics (Brown, 2010;Myrick, Willoughby, Noar, & Brown, 2013;Myrick et al, 2014).…”
Section: Celebrity Health Events and Health Educationmentioning
confidence: 99%
“…Research on publicized celebrity health events has long recognized the potential of these occasions to increase education and awareness of different health topics (Brown & Basil, 1995;Casey et al, 2003;Dean, 2016;Myrick, Noar, Willoughby, & Brown, 2014), but the role of SNS behaviors has not yet been thoroughly examined. Williams' passing provided an opportunity to examine how a parasocial grieving process, like any online mourning rituals, could have led to SNS behaviors that contributed to the spread of educational health information.…”
Section: Introductionmentioning
confidence: 99%